FAKTOR-FAKTOR YANG MEMENGARUHI PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA (Media Riset Akuntansi, 2022)
The purpose of this study was to examine the effect of murabahah financing, financing to deposit ratio (FDR), capital adequacy ratio (CAR), and non-performing financing (NPF) on the profitability Islamic commercial banks in Indonesia. In this study, the population were 84 in total registered with the Financial Services Authority (OJK) for 2015-2020 period. The sampling technique was purposive sampling.  This study used a multiple linear regression analysis. The results showed that murabahah financing and CAR had a positive effect on profitability. Besides that, NPF has a negative effect on profitability and FDR has no effect on profitability